ChatGPT - A critical view - Florian Allwein (IU Internationale Hochschule, 2024)
ChatGPT, a chatbot based on a Large Language Model, has become one of the fastest-growing consumer software applications in history. Discussion of the tool and its use cases contains an element of hype as it appears that the technology's capabilities are sometimes exaggerated. Moreover, a critical perspective is often lacking in research and practice. This paper points out some significant downsides, risks and limitations of using ChatGPT, arguing for a critical view of the tool based on ethics, regulations and reflected use. This can be used as a guideline for decisions on whether and how to use ChatGPT, and can inform future research.
Keywords: 004; ChatGPT; AI; Ethics